Microstructure and properties evolution of laser cladded B4C/Inconel 625 coatings by simultaneous ultrasonic impact - Lin Chen; Wei Chen; Xiuwei Tong; Lin Liu; Hao Li; Chunhuan Guo; Fengchun Jiang; Zubin Chen; Wenyao Sun; Yisen Liu; Chunyu Tan (Journal of Materials Research and Technology)
Simultaneous ultrasonic impact treatment (UIT) is employed to improve the tribological properties and microstructure of laser cladded B4C/Inconel 625 composite coatings on 316L stainless steel, based on prior optimization of linear energy density through controlling the molten pool morphology and porosity. The results demonstrate that the phase composition remains unchanged after being treated by UIT, whereas the diffraction peak intensity decreases significantly, suggesting microstructure refinement. UIT introduces plastic deformation into the coating, generating high density of dislocation tangles and walls that facilitate the recrystallisation process. After the UIT process, the original columnar crystals transform into equiaxed grains, with a significant reduction in dendritic crystals exceeding 490 μm in length. The elemental diffusion at the substrate-coating interface is more pronounced, suggesting a better metallurgical bonding. A substantial improvement in the microhardness and tribological properties is achieved due to the synergistic effect of dislocation strengthening and fine grain strengthening. The microhardness reaches 387.4 HV0.2, representing a 10.2 % increase compared to the coating without UIT. Meanwhile, the average coefficient of friction (COF) decreases by 33 %, from 0.96 ± 0.1 to 0.64 ± 0.11. Coatings without UIT experience abrasive, fatigue, and oxidative wear, whereas UIT-treated coatings predominantly exhibit milder oxidative and abrasive wear. The dislocation accumulation and recrystallisation induced by UIT provide a novel approach for preparing Ni-based coatings with superior properties.